Theoretical Investigation of Janus ReSSe Monolayers Doped with Cun Metal Clusters (n = 1-3) for Detecting Gases from Thermal Runaway Decomposition in Lithium-Ion Batteries - Zhang, Lang (Langmuir : the ACS journal of surfaces and colloids, 2025)
Effective detection and timely resolution of internal faults in lithium-ion batteries (LIBs) are necessary prerequisites for the safe use of batteries. In this study, the adsorption properties of four lithium-ion battery thermal runaway characteristic gases (CO, CH4, C2H2, and C2H4) on the surface of ReSSe monolayers modified with Cun (n = 1-3) clusters were systematically investigated based on first-principles calculations. The calculation results showed that the introduction of Cu1, Cu2, and Cu3 reduced the bandgap of the ReSSe monolayer to 0.077, 0.399, and 0.170 eV, respectively, and significantly enhanced the gas sensing performance of ReSSe. By calculating and analyzing parameters such as deformation charge density (DCD), energy band structure, density of states, molecular orbitals, sensitivity, and recovery time during gas adsorption, it was revealed that the Cu2-ReSSe system exhibited excellent adsorption capacity and sensing performance for C2H4. The adsorption energy and sensitivity reached -1.03 eV and 12.58, respectively. The recovery time of C2H4 on the Cu2-ReSSe surface was 10.93 s under the temperature condition of 398 K, which indicates that this material can realize the repeated detection of C2H4 at suitable temperatures, and it is an up-and-coming candidate for a C2H4 gas sensor. This study provides theoretical support for the application of Cu metal-cluster-anchored ReSSe-based materials in the field of lithium-ion battery fault detection